2017
DOI: 10.1038/nchem.2730
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular metamorphosis via stimulus-induced transformations of polymer architecture

Abstract: Macromolecular architecture plays a pivotal role in determining the properties of polymers. When designing polymers for specific applications, it is not only the size of a macromolecule that must be considered, but also its shape. In most cases, the topology of a polymer is a static feature that is inalterable once synthesized. Using reversible-covalent chemistry to prompt the disconnection of chemical bonds and the formation of new linkages in situ, we report polymers that undergo dramatic topological transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
162
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(168 citation statements)
references
References 31 publications
3
162
0
Order By: Relevance
“…A thermodynamically selective cycloaddition between maleimide and anthracene or furan functionalized polymers allowed for metamorphosis of linear amphiphilic block‐copolymers and hyperbranced polymers. This technique was applied to produce macroscopic gels which can transition between different density states based on temperature …”
Section: Functional Handles On Polymersomes and Nanoparticlesmentioning
confidence: 99%
“…A thermodynamically selective cycloaddition between maleimide and anthracene or furan functionalized polymers allowed for metamorphosis of linear amphiphilic block‐copolymers and hyperbranced polymers. This technique was applied to produce macroscopic gels which can transition between different density states based on temperature …”
Section: Functional Handles On Polymersomes and Nanoparticlesmentioning
confidence: 99%
“…Among different architectures of polymers, hyperbranched, or dendritic, polymers display unique structural features, such as internal cavities and a large number of functional groups in their periphery. As structure begets properties, [7] the presence of internal cavities enables encapsulation of small-molecule cargos like drugs. In addition, peripheral functional groups can serve as handles for further modifications with therapeutic molecules and/or targeting moieties.…”
mentioning
confidence: 99%
“…Transformation of shape and structure due to changes in surroundings (stimuli) is considered as fundamental condition of survival for living beings. As molecular architectures control the properties of materials, over the past few decades researchers have developed new materials with different architectures to mimic the nature . In this context, materials ranging from polymers to nanomaterials which can respond and adapt to environmental changes have attracted attention …”
Section: Association Constants (Ka) and Diffusion Coefficient Of The mentioning
confidence: 99%
“…In case of polymers, not only the size but also the architecture (shape) plays a pivotal role on the polymer properties like aggregation, flowability, strength, etc . With a change in their molecular architecture, their physical and chemical properties also change . Recently, Sumerlin et al successfully demonstrated “macromolecular metamorphosis” (change in macromolecular architecture) by using different Diels–Alder reactions .…”
Section: Association Constants (Ka) and Diffusion Coefficient Of The mentioning
confidence: 99%